1995
DOI: 10.1002/j.1460-2075.1995.tb06972.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-tubulin is required for the structure and function of the microtubule organizing centre in Drosophila neuroblasts.

Abstract: We report that in Drosophila, gamma‐tubulin is required for the structure as well as the function of microtubule organizing centres (MTOCs). This conclusion is based on the identification and phenotypic characterization of a mutant allele of the gamma‐tubulin gene located at region 23C of the polytene chromosome map. This mutation, which we have called gamma‐tub23CPl, is caused by the insertion of a P‐element within the 5′ untranslated leader of the gamma‐tubulin transcript. Northern and Western analysis show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 20 publications
4
130
0
Order By: Relevance
“…Cells of g-tubulin mutants isolated in animal, fungus, and yeast exhibit aberrant microtubule organization (Oakley et al, 1990;Horio et al, 1991;Sobel and Snyder, 1995;Sunkel et al, 1995). Defects in nuclear division observed during tubg1-1 tubg2-1 gametogenesis are consistent with abnormalities in microtubule nucleation and organization.…”
Section: Microtubule Defects During Mutant Pollen Developmentmentioning
confidence: 99%
“…Cells of g-tubulin mutants isolated in animal, fungus, and yeast exhibit aberrant microtubule organization (Oakley et al, 1990;Horio et al, 1991;Sobel and Snyder, 1995;Sunkel et al, 1995). Defects in nuclear division observed during tubg1-1 tubg2-1 gametogenesis are consistent with abnormalities in microtubule nucleation and organization.…”
Section: Microtubule Defects During Mutant Pollen Developmentmentioning
confidence: 99%
“…We counterstained spermatids with GFPpericentrin-AKAP450 centrosomal targeting (PACT; a centriole-targeting domain found in D-PLP; Gillingham and Munro, 2000;Martinez-Campos et al, 2004) to label basal bodies and found that Bld10 localized to the rod-shaped basal body, which is surrounded by the centriolar adjunct (Tates, 1971), a collar-like PCM structure that contains ␥-tubulin (Figure 2, C and D; Sunkel et al, 1995;Wilson et al, 1997). Bld10 was concentrated at the proximal and distal ends of the basal body, with lower expression at the region encircled by the centriolar adjunct ( Figure 2, C and D).…”
Section: Bld10 Is a Centriolar And Sperm Basal Body Proteinmentioning
confidence: 99%
“…Under these conditions, centrosomes in Caenorhabditis elegans and Drosophila embryos were compromised in their ability to form mitotic asters (Hannak et al, 2002;Strome et al, 2001), separate from one another (Barbosa et al, 2003;Sampaio et al, 2001), and organize meiotic and mitotic spindles (Sunkel et al, 1995;Barbosa et al, 2000Barbosa et al, , 2003. It is of interest that mitotic asters in some of these systems formed in the absence of ␥ tubulin or other ␥ tubulin ring complex proteins (Strome et al, 2001;Hannak et al, 2002;Barbosa et al, 2003).…”
Section: Centrosomal Anchoring Of ␥ Turcs By Pericentrin Is Required mentioning
confidence: 99%